GLAND ENZYMES SECRETION. - Bakhtiyar. Bakhshullayevich. Takhirov.; Zarnigor. Kakhorova. (European Journal of Agricultural and Rural Education, 2024)
The article describes the anatomo-morphology of the pancreas and its age-related features, pancreatic insufficiency